Bougainville before the conflict - J Regan, Anthony (ANU Press, 2015)
One of the most beautiful island groups of the Pacific, Bougainville has a remarkable history. Tragically, it is as the site of devastating civil conflict that Bougainville is perhaps best known. In exploring the rich environmental, cultural and social heritage of Bougainville before the conflict, this collection provides an insight into the long-term causes of the crisis. In doing so, it surveys such topics as Bougainville's prehistory and traditional cultures, the impact of German and Australian colonialism, the attempts by disparate local cultures to find a common identity, the assertion of political autonomy in the face of coercion to integrate with Papua New Guinea, and contemporary efforts to resolve conflict and plan a viable future. A landmark collaboration between expert commentators on Bougainville and Bougainvilleans themselves, this volume provides a comprehensive picture for those seeking to understand Bougainville's history and future directions. Bougainville before the conflict was published in association with the State, Society and Governance in Melanesia Project, which is supported by The Australian National University and the Commonwealth of Australia.